Storming the tulips - Sanders, Ronald (Stonebrook Publ., 2011)
Presents the stories of twenty students who attended the First Montessori School in Amsterdam during the Holocaust, discussing the hardships and tragedies the children faced when friends and family members disappeared, some were sent to death camps, some joined the Nazi youth, and some struggled to find food
Includes bibliographical references (p. 164)
Keywords: Geschichte 1900-2000; World War, 1939-1945 / Personal narratives, Dutch; Children / Netherlands / Amsterdam / Biography; Students / Netherlands / Amsterdam / Biography; Children and war / Netherlands / Amsterdam / History / 20th century; Holocaust, Jewish (1939-1945) / Netherlands / Amsterdam; Holocaust, 1939-1945 / Personal narratives; Jewish children in the Holocaust / Amsterdam (Netherlands) / Biography; Geschichte; Kind; Weltkrieg (1939-1945); Montessori-Schule; Zweiter Weltkrieg; Besetzung; Judenverfolgung; World War, 1939-1945 / Netherlands / Amsterdam; Amsterdam (Netherlands) / Biography; Niederlande; Biografie; Erlebnisbericht